REPRESENTASI CITRA PEREMPUAN JAWA DALAM FILM PUTERI GUNUNG LEDANG KARYA SAW TEONG HIN - Ilhamsyah, Ade; Yazid, Tantri Puspita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The film as a work of art is often interpreted the results of copyrighted works of art that have the completeness of some of the elements of art to meet the needs of a spiritual nature . The position of women often appears as a symbol of subtlety , emotional , something that moved slowly , sometimes even stops . Women are so close to the idiom - phrases such adversity , oppression , even in the